Effects of February 6, 2023 Kahramanmaraş Earthquakes on Housing Preferences vis-à-vis Sociology of Disasters - Nihal Arda Akyıldız; Aykut Sığın (Journal of Economy Culture and Society)
On February 6, 2023, two major earthquakes occurred in Kahramanmaraş, Türkiye. This study analyzes the transformations in housing preferences of the earthquake victims. Accordingly, 30 earthquake victims who were in Adana, Hatay, Kahramanmaraş, and Malatya during the earthquakes were reached via snowball sampling, and then semistructured interviews were conducted with them. After transcribing the interviews, the software ATLAS.ti 9 was used to identify the five themes of the study: 1) preferences shifting from vertical to horizontal housing, 2) preferences shifting from comfort-oriented options to those with safety, 3) preferences shifting from urban to rural areas, 4) rising demand for buildings complying with the earthquake legislation, and 5) reasons for not leaving the earthquake zone because of economic or family reasons despite lack of trust in the building/area. The findings revealed that safety needs were prioritized over other needs, supporting Maslow’s theory of hierarchical structuring of needs. This study might make a general contribution to the field of sociology of disasters and guide development of public policies postdisaster.